Role of khilṭ-i-Safrā in digestion: scientific exploration - Khan, Sajid; Imam, Ashraf; Lari, Qamrul Hasan (International Journal of Research in Medical Sciences, 2025)
The Unani system of medicine is based on the concept of Akhlāt (humors), which includes khilṭ-i-Safrā (yellow bile), a vital bodily fluid primarily produced by the liver and stored in the gallbladder. Khilṭ-i-Safrā plays a crucial role in digestion and overall physiological balance. It is characterized as hot and dry (Ḥārr Yābis) in temperament and is responsible for tarqeeq dam of blood, promoting circulation, and supporting the digestive process. Khilṭ-i-Safrā is known for its detersive (cleansing) action in the intestine also influences the enteric nervous system (ENS), stimulating peristaltic movements and enhancing gastrointestinal secretions. This function aligns with the concept of digestion in Unani system of the medicine, where balanced khilṭ-i-Safrā ensures smooth digestion and excretion. The study explores the classical Unani perspective of khilṭ-i-Safrā and its correlation with bile in modern physiology, highlighting its essential role in digestion. In modern medical terms, bile, a secretion of the liver stored in the gallbladder and released into the intestine, which is considered as a component of khilṭ-i-Safrā in Unani system of the medicine. Bile salts facilitate the digestion and absorption of fats by emulsifying fat globules and forming micelles, making them more accessible for enzymatic action. Additionally, bile acts as a natural laxative by stimulating intestinal peristalsis.